Full Inclusive Genetic Programming - Marchetti, Francesco (2024)
Marchetti, F., Castelli, M., Bakurov, I., & Vanneschi, L. (2024). Full Inclusive Genetic Programming. In 2024 IEEE Congress on Evolutionary Computation (CEC) (pp. 1-8). Institute of Electrical and Electronics Engineers (IEEE). https://doi.org/10.1109/CEC60901.2024.10611808 --- This work was partially supported by FCT, Portugal, through funding of research unit MagIC/NOVA IMS (UIDB/04152/2020); and by the SPECIES Society through the SPECIES Scholarship 2022.